Assessment of River Herring Spawning Runs in a Chesapeake Bay Coastal Plain Stream using Imaging Sonar. Issue 1 (2nd January 2017) - Ogburn, Matthew B.; Spires, Jason; Aguilar, Robert; Goodison, Michael R.; Heggie, Keira; Kinnebrew, Eva; McBurney, William; Richie, Kimberly D.; Roberts, Paige M.; Hines, Anson H.
Abstract: Recent declines in anadromous river herring (Alewife Alosa pseudoharengus and Blueback Herring A. aestivalis ) have been documented in much of their range using fishery-independent spawning run counts. A lack of rigorous long-term run counts and demographic data for Chesapeake Bay spawning stocks resulted in the declaration of unknown stock status in a 2012 stock assessment and made it difficult to evaluate responses to conservation and restoration efforts. The objectives of the present study were to (1) conduct the first spawning run counts of river herring in the Choptank River, Maryland, since the run counts performed over a 2-year period in 1972 and 1973, (2) evaluate population structure and dynamics, and (3) identify environmental variables associated with run timing. Spawning runs of Alewives and Blueback Herring were recorded from March 10 to June 4, 2014, using imaging sonar and processed manually to produce hourly run counts of fish with TLs ranging from 200 to 350 mm. A total of 1, 659, 090 ± 91, 250 fish with TLs of 200–350 mm (errors estimated using a CV of 5.5%) were estimated to swim upstream past the sonar unit. Boat electrofishing was conducted at weekly intervals to estimate species composition and obtain samples for demographic analysis. Using these species composition data to apportion run counts resulted in an estimated count of 581, 275 ± 31, 970 Alewives and 726, 450 ± 39, 955 Blueback Herring. Fish age by otolith analysis varied from 2 to 7 years and total instantaneous mortality ( Z ) was estimated at 1.47 (SE, 1.8 × 10 −5 ) for Alewives and 1.91 (SE, 1.1 × 10 −5 ) for Blueback Herring. Upstream migration occurred primarily in the afternoon and evening associated with increasing water temperature, and downstream migration occurred at low and decreasing levels of discharge. The present study established a new fishery-independent population monitoring effort for river herring in Chesapeake Bay and identified associations between environmental drivers and upstream and downstream movements. Received March 8, 2016; accepted August 31, 2016